The reliability of potential fatigue-monitoring measures in elite youth soccer players - Fitzpatrick, J. F.; Hicks, K. M.; Russell, M.; Hayes, P. R. (The Journal of Strength and Conditioning Research, 2021)
Monitoring fatigue is of vital importance to practitioners; however, logistics and concerns about reliability may impede the use of certain measures. This study aimed to quantify the reliability of potential measures of fatigue; a subjective wellness questionnaire, jump performance tests, and tri-axial accelerometer variables derived during submaximal shuttle running in elite youth soccer players. A secondary aim was to establish the minimum test duration that could be used for the submaximal shuttle run while maintaining good reliability. Seventeen male youth team players (age: 17.4 ± 0.5 years) were assessed on 2 occasions, spaced 7 days apart. Typical error, coefficient of variation (CV%), interclass correlation (ICC), and minimum detectable change were calculated for a subjective wellness questionnaire, countermovement jump (CMJ), squat jump (SJ) and drop jump contact time (DJ-CT), drop jump height (DJ-JH), and reactive strength (DJ-RSI). A novel submaximal shuttle running test was also used to assess tri-axial accelerometer data reliability. Results suggest that CMJ, SJ, DJ-CT, and DJ-RSI have good test-retest reliability (CV% = 4.5-7.7; ICC = 0.80-0.88); however DJ-JH did not show acceptable reliability (CV% = 6.0; ICC = 0.76). Good reliability was found for all tri-axial accelerometer variables during a 3-minute (2-minute analysis) submaximal shuttle run (CV% = 2.4-8.0; ICC = 0.81-0.95), except for % PlayerLoad anterior-posterior (%PLAP) (CV% = 7.2; ICC = 0.63). The subjective wellness questionnaire demonstrated poor reliability for all items (CV% = 11.2-30.0; ICC = 0.00-0.78). The findings from this study provide practitioners with valuable information about the reliability of a range of potential fatigue-monitoring measures. This can be used to help make accurate decisions about the magnitude of change in these assessments when used in practice.